Extremely Low Birth Weight Predisposes to Impaired Renal Health: A Pooled Analysis - Maja Gilarska; Anke Raaijmakers; Zhen-Yu Zhang; Jan A. Staessen; Elena Levtchenko; Małgorzata Klimek; Andrzej Grudzień; Katarzyna Starzec; Karel Allegaert; Przemko Kwinta (Karger Publishers, 2019)
Background: A number of studies examined the association between preterm delivery and kidney size and function later in life. However, the number of cases in published cohort studies is low. This study was aimed at performing a multicenter collaboration to pool data to obtain more accurate results to quantify the extent of renal impairment in former extremely low birth weight (ELBW; <1,000 g) children. Methodology: We performed a subject-level meta-analysis to pool data from Cracow (64 cases/34 controls) and Leuven (93 cases/87 controls). We assessed and analyzed cystatin C, estimated glomerular filtration rate (eGFR), ultrasound kidney length, and blood pressure (BP) in 11-year-old ELBW children compared with controls born at term. The prevalence of hypertension (HT) and prehypertension (preHT) in both groups was also analyzed. Results: The study group comprised 157 former ELBW children (gestational age 23-33 weeks and birth weight 430-1,000 g) and 123 children born at term. Former ELBW children had lower mean eGFR (100.62 ± 16.53 vs. 111.89 ± 15.26 mL/min/1.73 m2; p < 0.001), smaller absolute kidney length (8.56 ± 0.78 vs. 9.008 ± 0.73 cm; <0.001), and higher systolic (111.8 ± 9.8 vs. 107.2 ± 9.07 mm Hg; p = 0.01) and diastolic (68.6 ± 6.8 vs. 66.3 ± 7.7 mm Hg; p = 0.03) BP. Smaller renal size in former ELBW children was positively associated with lower birth weight, shorter gestational age, and severity of perinatal complications (intraventricular hemorrhage, length of stay, mechanical ventilation, and oxygen therapy). Conclusion: ELBW is associated with lower eGFR and a high frequency of preHT and HT.